Water Resources Accounting in Arid Zone of Northwest China: A Case Study of Integrated Environmental and Economic Accounting - Chen, Dongjing; Gheng, Guodong; Xu, Zhongmin; Wan, Alice; Chen, Rensheng (Annals of Arid Zone, 2016)
Water resources play an important role in production, survival, and maintenance of environmental functions. Water resourcesÂ· accounting is an important part of integrated environmental and economic accounting. Based on the introduction of the System of Integrated Environmental and Economic Accounting (SEEA), we take Zhangye Prefecture, which lies in the arid zone of Northwest China, as a . case to illustrate the process of water resources accounting. Water resources accounts include a physical account, monetary account and allocation of water depletion cost account. The results show that the depletion cost of excessive water use was equivalent to 197.93 million RMB in Zhangye Prefecture for the year 2000, and the net domestic product (NDP), deducting water depletion cost (EDP), was 3.56% less than the NDP. Water depletion cost accounted for 9.39% of the traditional net capital formation.